RING MATRIKS ATAS RING KOMUTATIF - Abdurrazzaq, Achmad; Wardayani, Ari; Suroto, Suroto (Jurnal Ilmiah Matematika dan Pendidikan Matematika; Vol 7 No 1 (2015): Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2015)
This paper discusses a matrices over a commutative ring. A matrices over commutative rings is a matrices whose entries are the elements of the commutative ring. We  investigates the structure of the set of the matrices over the commutative ring. We obtain that the set of the matrices over the commutative ring equipped with an addition and a multiplication operation of matrices is a ring with a unit element.